Thermophoresis and Brownian motion effects on the Casson ternary hybrid nanofluid over a horizontal plate containing gyrotactic microorganisms - N. Ramya; M. Deivanayaki; Sakthivel Pandurengan (Chemical Physics Impact)
This study explores the behavior of fluids containing gyrotactic microorganisms over a horizontally shrinking or stretching plate, focusing on thermophoresis and Brownian motion effects. Thermophoresis improves fluid flow and thermal conductivity, whereas Brownian motion decreases velocity but raises concentration profiles, according to numerical solutions to the governing nonlinear partial differential equations. Although microorganism density increases the Sherwood number, which indicates better mass transfer, it has a detrimental effect on concentration. As stretching rates increase, the Nusselt number rises as well, indicating improved heat transmission. Stronger magnetic fields in stretching situations improve temperature profiles while decreasing concentration, velocity, and microbe density. The results show that, in comparison to conventional and hybrid nanofluids, Casson ternary hybrid nanofluids provide better thermal energy transfer.